ANTONYM IN “THE GOBLIN OF ADACHIGAHARA” FABLE BY YEI THEODORA OZAKI - Nafiisah Khan; Mayadrie Aidhi Aridzki; Luthfi Abbas; Emeliya Sukma Dara Damanik (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to analyze the antonyms contained in the Fable